OPTIMALISASI PEMBELAJARAN SEJARAH MELALUI PEMANFAATAN MEDIAAUDIO VISUAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA SMA TARUNA NUSANTARA KELAS XI IATAHUN AJARAN 2012/2013 - Hastuti, Tri Puji; Budiyono, B.; Joebagio, Hermanu (HISTORIKA, 2016)
Background: Innovation and improvisation in learning the use of history in the form of audio-visual media can be an alternative to overcome the problems of saturation in learning so that students are expected to increasingly keen to explore the lessons and learning outcomes can be achieved in the history of this diharapkan.Penelitian aims to increase the activity of teachers, students, and the learning process with the history and use of audio-visual media constructivism approach and models kelompokdi discussion Taruna Nusantara XI IPS1 Magelang regency.Methods: This is a Class Action Research (CAR) with the object of research siswaSMA Taruna Nusantara XI IPS1 Magelang District in the second semester of the 2012/2013 academic year. Data were collected through observation, document review and analysis of qualitative descriptive. To give meaning success of the measures used relative criteria that action is considered successful if there is an increase from the previous learning processes. This study was conducted over three rounds (cycle) and learning strategies, improvements in each cycle.Results: The use of audio-visual media combined with a constructivist approach and model of group discussions can increase the activity of teachers, students, learning and growing interest in learning so that the learning achievement increased. Therefore, this model should be done as a learning model variations subjects Sejarahsehingga students feel happy that affect the formation of learning fun and a high interest in learning. The success of this study occurred on the third cycle with pre testnya learning outcomes is the number 2055, an average of 79, the highest score of 90, the lowest value of 60, the number of values under KKM 11, 57.7% completeness. While the results of post test total value of 2090, an average of 80.40 the highest score of 100, the lowest value of 45, the student does not complete the KKM by 5 students, and the percentage of 80.8% completeness.In a presentation with audio-visual media in small groups to create a great responsibility to concentrate and understand the material so that the attention of students in 100%.Â